Joy! Shout!' dance concert, Feb. 15 -23 - Uribes, Tom::::::::: (2013)
Fresno State's Contemporary Dance Ensemble will perform 'Joy! Shout!,' a contemporary dance concert 8 p.m. Feb. 15-16 in the John Wright Theatre.